2014
DOI: 10.1590/1413-78522014220600973
|View full text |Cite
|
Sign up to set email alerts
|

GCT: What happened after 10 years of curettage and cement? Retrospective study of 46 cases

Abstract: OBJECTIVE: To compare the functional outcome of patients with and without arthrosis, and to determine whether the development of arthrosis is related to the distance of the tumor from the subchondral bone. METHODS: Forty six patients treated for Giant-cell tumor (GCT) between 1975 and 1999 met inclusion criteria. GCT was diagnosed by percutaneous biopsy and confirmed after resection, in all cases. Campanacci's and Kellgren's classification, the distance of the cement to the articular surface and MSTS score wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Baptista et al showed that subchondral lesions, <10 mm from the articular cartilage, are 8 times more likely to progress to arthrosis when treated with solid cement implantation, probably due to cement loosening. 8 This loosening was well documented in this study by bone resorption around the block and a fibrous layer formation. Owing to the lack of mechanical support, subchondral bone and the articular surface may fracture or deform leading to osteoarthritis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Baptista et al showed that subchondral lesions, <10 mm from the articular cartilage, are 8 times more likely to progress to arthrosis when treated with solid cement implantation, probably due to cement loosening. 8 This loosening was well documented in this study by bone resorption around the block and a fibrous layer formation. Owing to the lack of mechanical support, subchondral bone and the articular surface may fracture or deform leading to osteoarthritis.…”
Section: Discussionsupporting
confidence: 74%
“…The subchondral position of the defect created a critical mechanical as well as biological situation. Baptista et al showed that subchondral lesions, <10 mm from the articular cartilage, are 8 times more likely to progress to arthrosis when treated with solid cement implantation, probably due to cement loosening . This loosening was well documented in this study by bone resorption around the block and a fibrous layer formation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The use of bone cement is a well-established method that presents good long-term oncological and functional results. Regarding the possibility of arthrosis secondary to the use of bone cement, Baptista et al 4 published a retrospective study of 46 cases of GCT undergoing curettage and cementation, concluding that the distance from cement to subchondral bone has a prognostic relationship to the development of osteoarthritis, but not to final functional outcome of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Type III are aggressive, extending throughout the periosteum and surrounding tissues. 3 , 4 , 5
Fig. 1 Campanacci classification.
…”
Section: Introductionmentioning
confidence: 99%